2023
DOI: 10.1089/apc.2022.0225
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Retention in HIV Care: A Study Within a Review

Abstract: Globally, there are more than 37.7 million people living with HIV (PLHIV). Retention in human immunodeficiency virus (HIV) care is a common and modifiable determinant of increased adherence to antiretroviral therapy (ART), better health outcomes, and a better quality of life.There is no consensus in the literature on measures of retention in HIV care. This makes it very difficult to compare different studies and jurisdictions. This thesis review summarizes the definitions of retention used in randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 90 publications
(214 reference statements)
0
9
0
Order By: Relevance
“…Due to the lack of a standard definition 22 and limited existing data on the complete HIV care continuum in rapid start, 14 we evaluated 2 different measures of retention in care. In our study, rapid start was associated with improved retention in care when measured by the current HRSA definition (one clinic visit and one viral load at least 90 days apart) but did not impact continuous retention in care (one medical visit in each 6-month period at least 60 days apart).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of a standard definition 22 and limited existing data on the complete HIV care continuum in rapid start, 14 we evaluated 2 different measures of retention in care. In our study, rapid start was associated with improved retention in care when measured by the current HRSA definition (one clinic visit and one viral load at least 90 days apart) but did not impact continuous retention in care (one medical visit in each 6-month period at least 60 days apart).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we conducted a SWAR to identify definitions of retention used in RCTs. This review showed a wide heterogeneity in the definitions of retention [18]. We anticipate that this mixed-method approach will provide the breadth and depth of the topic and will advance efforts towards a standard measure of retention in care.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed method approach will comprise two phases. In the qualitative phase, we will conduct in-depth interviews building upon retention in care definitions identified in a prior review [18]. In the qualitative phase, we will explore participants’ views on measuring retention with the intent of using this information to develop a survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations